DESIGN AND DEVELOPMENT OF A PV INVERTER SYSTEM WITH A REAL POWER CONCEPT FOR INDUCTION MOTOR LOADS - Hadiyanto Hadiyanto; Ali Abrar; Syahruddin Syahruddin; Muhammad Rifaldy Zhaqi (Multica Science and Technology, 2025)
The type of inverter used greatly affects the efficiency of the PLTS in distributing electrical power to the load to be used. The use of an inappropriate inverter type will cause electrical equipment to quickly become damaged [4]. This study was conducted to help determine the type of inverter that is more appropriate for use in a PLTS system with inductive and resistive loads, so that the quality of the electrical power produced is maximized. This study compared the 1000 Watt Pure Sine Wave Inverter and the 1000 Watt Modified Sine Wave Inverter by measuring the waveform, voltage output value, current output value, power output value, voltage Total Harmonic Distortion (THD) value and current Total Harmonic Distortion value. The final results of the study showed that the Pure Sine Wave Inverter was superior in producing output power, had lower voltage and current distortion values and could produce output waves with a pure sine shape